Phytosome as Cytotoxic Agent Delivering System : A Review - Widyandani Sasikirana; Eva Annisaa'; Nuraini Ekawati (Diponegoro University, 2021)
Along with the rapid development of herbal medicine formulas, an appropriate drug delivery system is needed to increase its bioavailability. One of them was used the phytosome. As a delivery system, it was known to be able to increase the bioavailability of phytomedicine by increasing the permeability of herbal compounds on cell membranes so the absorption of the compound will be increased. In its development, the phytosome formula was effective for delivering cytotoxic agent compounds, such as quercetin, diosgenin, icariin, tocopherol, and others. Besides, some of these formulas have also been commercialized and patented. The effectiveness and ease of manufacture have made phytosomes a promising drug delivery system in the development of cytotoxic drugs.